Another step in unravelling Deronectina larval morphology: descriptions of Boreonectes griseostriatus griseostriatus (De Geer, 1774) and Nectoboreus aequinoctialis (Clark, 1862) (Coleoptera: Dytiscidae, Hydroporinae) with phylogenetic considerations - Alarie, Yves; Michat, Mariano C. (Zootaxa, 2026)
Larval morphology of the Holarctic Boreonectes griseostriatus griseostriatus (De Geer, 1774) and of the Nearctic endemic Nectoboreus aequinoctialis (Clark, 1862) is described based on ex ovo material. General morphology and chaetotaxy of the cephalic capsule, head appendages, legs, terminal abdominal segment and urogomphi are described and illustrated for first and third instar. Phylogenetic comparison of Boreonectes Angus, 2010 and Nectoboreus Fery & Ribera, 2018 with nine other Deronectina genera was conducted in a cladistic context. Both genera are similar sharing several character states (e.g., presence of an elongate primary seta PA3, prementum non-sclerotized dorsally, presence of natatory setae on legs, elongate urogomphi, and presence of several non-sclerotized annuli on instar III urogomphomere 1) suggesting a closer relationship with Leconectes Fery & Ribera, 2018 and Mystonectes Fery & Ribera, 2018. Instar I larvae of Leconectes and Nectoboreus Fery & Ribera, 2018 share two unique character states: presence of additional setae on legs and presence of one non-sceloritized annulus on urogomphomere 1.